Antecedents of livelihood of entrepreneurs at the disaster-hit areas of Sindh, Pakistan. - Kazi, Abdul Ghafoor (2017)
Pakistan is an underdeveloped country and prone to natural disasters. A natural disaster destroys livelihood, causing death and scarcity of food, shelter, water, gas, education, jobs, health and infrastructure. Previous research shows that the aid from the government and the international community is a temporary relief, whereas entrepreneurship could provide a permanent solution for livelihood restoration because it generates jobs for the affected people. The main objective of this study is to examine the role of entrepreneurship in restoring livelihood through firm‘s performance and government support at the disaster-hit areas (district Dadu and Jamshoro) of Sindh, Pakistan. This is a quantitative research that used Sustainable Livelihood Approach (SLA) to develop the research framework. A total of 928 most affected entrepreneurs were selected as a sample by using multistage sampling technique. Questionnaires were used in data collection and the data collected was analyzed using covariance-based structural equation modeling for data analysis. The results showed that the entrepreneurship can restore livelihood through innovation skills, risk-taking, and proactiveness; whereas better firm performance could help other people to restore their livelihood. Additionally, the government support strengthens firms performance and create a sustainable livelihood for among entrepreneurs and their community. This study has contributed to the body of knowledge by testing SLA in an underdeveloped country. The findings could also aid policymakers to update policies related to livelihood restoration by including training for entrepreneurs as a contingency plan and backup plan for the business to cope with natural disasters. Furthermore, managers in disaster management can focus on entrepreneurship promotion when implementing a disaster management project. Thus, this study concludes and suggests that the entrepreneurship can be used for livelihood restoration program in a disaster-hit area particularly in the underdeveloped countries.